A survey of network protocol based steganographic techniques - Abdullaziz, O.; Goh, V.; Ling, Huo Chong; Wong, K. (2014)
Steganography is a sub-discipline of information hiding, which hides external information into an innocuous carrier to establish stealthy communication. Steganography in network protocols however, is an emerging research area, which exploits network protocols specifications, protocol mechanisms, network applications, and network services to realize covert channels between network end-systems. In this paper, we aim to clarify topics related to information hiding and its applications especially steganography. We also provide a brief comparison between steganography and cryptography. Eventually, we categorize and present some of the current work related steganography in networks.